Potential over request in anemia laboratory tests in primary care in Spain. Issue 6 (July 2015) - Salinas, María; López-Garrigós, Maite; Flores, Emilio; Uris, Joaquín; Leiva-Salinas, Carlos
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives The aim was to study the inter-practice variability in anemia laboratory tests requested by general practitioners in Spain, to evaluate for a potential requesting inappropriateness. Methods Laboratories from diverse Spanish regions filled out the number of cell blood count, ferritin, folate, iron, transferrin, and vitamin B12 requested by general practitioners during 2012. The number of test requests per 1000 inhabitants and ratios of related tests requests were calculated. The results obtained in hospitals from different areas (urban, rural, or urban–rural), type of management (public or private), and geographic regions were compared. Results There was a high variability in the number of test requests and ratios of related tests. Cell blood count was over requested in rural areas and in hospitals with private management. Andalucía was the community with the lowest number of iron requests and the lowest folate/vitamin B12 indicator value. Conclusions Iron and transferrin seemed over requested in some areas; as were folate and ferritin when compared to vitamin B12 and cell blood count, respectively. The differences observed between areas indicate that other factors besides clinical reasons could be behind that variability and emphasize the need to accomplish interventions to improve the appropriate use of anemia laboratory tests.